Zastosowanie bloga we wspieraniu refleksji studenckiej podczas praktyk pedagogicznych - Pitura, Joanna (Neofilolog, 2017)
The article concerns pre-service English language teacher training and discusses some results of an on-going action research project, the aim of which is to investigate a way of supporting student reflection while they do obligatory teaching practice in Polish state schools. The paper presents the design of the “Develop by Blogging” intervention, as well as its pilot implementation. Preliminary findings suggest that the intervention has the potential to create time and space for reflection on individual professional experience and can constitute a chance for enhancing reflection among pre-service teachers.